Organization of coordinated functioning of various types of passenger transport in transport-interchange hubs - Moskvichev, Oleg; Leonova, Svetlana (Nexo Revista Científica, 2021)
The article deals with the organization of high-quality interaction of various types of passenger transport in the transport- interchange hub. Urban and regional interchange hubs are being studied. A methodology based on the use of quantitative methods and implemented with the help of software products (the developed program "Effective transfers" and the well-known simulation modeling programs PTV Visum, AnyLogic) is suggested. This method is applicable for any city and includes 3 stages. At the first stage, the number of passengers in the transport-interchange hubs who transfer from one type of urban public transport to another is predicted; the direction of passenger traffic is determined; urban routes that require schedule approval are chosen. At the second stage, the number of passengers who use the considered transport-interchange hub to transfer from suburban, intercity transport to urban modes of transport is predicted. At the third stage, the schedule of all types of transport is coordinated; the need for rolling stock is determined; passenger traffic is modeled and studied at the hub in order to rationally organize the planning structure of the transport-interchange hub. The obtained scientific results can be used in the design of a system of transport and transfer hubs and planning the placement of transport and social facilities on the territory of the transport-interchange hub.